The Influence of Islamic Religious Education on Students’ Mental Health Awareness - Muhammad Iftor Ramadhan; Abdul Wahab Karim; Ahadiah Agustina (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the influence of Instagrammable aesthetics and halal travel ethics on the travel preferences of Muslim Generation Z (Gen Z), specifically among students of Sharia Economics and Islamic Communication Studies at Universitas Muhammadiyah Mataram. The phenomena of Instagrammable tourism, which emphasizes visual appeal, along with the growing awareness of halal travel principles in destination selection, are key factors shaping Gen Z’s travel preferences, who are highly active on social media. This research employs a quantitative descriptive-explanatory approach using a Likert scale questionnaire validated for reliability and validity. A purposive sampling technique was used to select 150 respondents. The results of multiple linear regression analysis indicate that although Instagrammable aesthetics and halal travel ethics have a positive influence on Gen Z’s travel preferences, the effects are minimal and statistically insignificant. This study fills a gap in the literature regarding the interaction between visual aesthetics and halal principles in the context of halal tourism in the social media era. It also offers practical implications for developing destination marketing strategies that incorporate both aesthetic values and Sharia ethics for young Muslim travelers. The study recommends sustainable and inclusive tourism development by integrating aesthetic appeal and halal ethics.